Building tolerance by dismantling synapses: inhibitory receptor signaling in natural killer cells. Issue 1 (19th December 2012) - Huse, Morgan; Catherine Milanoski, S.; Abeyweera, Thushara P.
Summary: Cell surface receptors bearing immunotyrosine‐based inhibitory motifs (ITIMs) maintain natural killer (NK) cell tolerance to normal host tissues. These receptors are difficult to analyze mechanistically because they block activating responses in a rapid and comprehensive manner. The advent of high‐resolution single cell imaging techniques has enabled investigators to explore the cell biological basis of the inhibitory response. Recent studies using these approaches indicate that ITIM‐containing receptors function at least in part by structurally undermining the immunological synapse between the NK cell and its target. In this review, we discuss these new advances and how they might relate to what is known about the biochemistry of inhibitory signaling in NK cells and other cell types.